2018
DOI: 10.1093/hmg/ddy246
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of FOP/FGFR1OP in mice recapitulates human short rib-polydactyly ciliopathy

Abstract: Skeletal dysplasias are a clinically and genetically heterogeneous group of bone and cartilage disorders. A total of 436 skeletal dysplasias are listed in the 2015 revised version of the nosology and classification of genetic skeletal disorders, of which nearly 20% are still genetically and molecularly uncharacterized. We report the clinical and molecular characterization of a lethal skeletal dysplasia of the short-rib group caused by mutation of the mouse Fop gene. Fop encodes a centrosomal and centriolar sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…However, these events were very infrequent, and the majority of satellites displayed short-range diffusive motility. Although previous studies described the bimodal motility for satellites qualitatively, the predominant diffusive behavior of satellites has not been reported 37,66,70 . This result has important implications for our understanding of satellite mechanisms.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, these events were very infrequent, and the majority of satellites displayed short-range diffusive motility. Although previous studies described the bimodal motility for satellites qualitatively, the predominant diffusive behavior of satellites has not been reported 37,66,70 . This result has important implications for our understanding of satellite mechanisms.…”
Section: Discussionmentioning
confidence: 78%
“…There is heterogeneity in the composition of individual satellites, and CCDC66 localizes only to a subset of satellites 15,43,65 . To investigate whether the dynamics of CCDC66-positive satellites are representative of all satellites in cells, we performed time-lapse imaging experiments in HeLa Kyoto cells stably expressing GFP-PCM1 from a bacterial artificial chromosome (BAC) transgene, which was recently used to study the function of FGFR1 oncogene partner (FOP) on satellite dynamics 66,67 . Representative satellites and their trajectories are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the roles of FOP in cilia assembly and disassembly are not fully understood. Although several recent studies have reported that near complete silencing of FOP inhibited primary cilia formation (Kanie et al, 2017;Mojarad et al, 2017;Cabaud et al, 2018), others found that moderate knockdown of FOP did not affect ciliogenesis (Graser et al, 2007;Lee and Stearns, 2013). Here we have demonstrated that FOP negatively regulates ciliogenesis based on the following evidence: firstly, the expression of FOP is inversely correlated with ciliogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…FOP is a centrosomal and centriolar satellites protein and is involved in multiple biological processes, such as MT anchoring, ciliogenesis, cell cycle progression, and cancer development (Yan et al, 2006;Mano et al, 2007;Acquaviva et al, 2009;Lee and Stearns, 2013;Kanie et al, 2017;Mojarad et al, 2017;Cabaud et al, 2018). However, the roles of FOP in cilia assembly and disassembly are not fully understood.…”
Section: Discussionmentioning
confidence: 99%